Violent crime: clinical and social implications - Ferguson, Christopher J. (SAGE, 2010)
Violent crime research : an introduction / Christopher J. Ferguson -- Family and social influences on violent crime / John C. Kilburn, Jr., and Jenifer Lee -- Media violence effects and violent crime / Christopher J. Ferguson -- Evolutionary and genetic explanations of violent crime / Martin Gottschalk and Lee Ellis -- The biochemistry of violent crime / Kevin M. Beaver -- Brain injuries and violent crime / Jose Lecentn-Carricentn and Francisco Jose Chacartegui-Ramos -- Violence among school-aged youth / Cricket Meehan and Patricia Kerig -- Violence and the elderly / Jeanette M. Daly -- Domestic violence research, policy, and practice / Sarah L. Desmarais, Andreas Gibas, and Tonia L. Nicholls -- Physical child abuse / Mary E. Haskett, Sharon G. Portwood, and Kristen M. Lewis -- Sex offenders : rape and child sexual abuse / Karen J. Terry ... [et al.]